2018
DOI: 10.1186/s12959-018-0185-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of rivaroxaban in children using physiologically based and population pharmacokinetic modelling: an EINSTEIN-Jr phase I study

Abstract: BackgroundThe EINSTEIN-Jr program will evaluate rivaroxaban for the treatment of venous thromboembolism (VTE) in children, targeting exposures similar to the 20 mg once-daily dose for adults. A physiologically based pharmacokinetic (PBPK) model for pediatric rivaroxaban dosing has been constructed.MethodsWe quantitatively assessed the pharmacokinetics (PK) of a single rivaroxaban dose in children using population pharmacokinetic (PopPK) modelling and assessed the applicability of the PBPK model. Plasma concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 21 publications
3
66
0
1
Order By: Relevance
“…Figure shows a recent example of PBPK predictions for children that was later confirmed in a clinical trial from a pediatric development program. Figure shows the single‐dose exposure (expressed as area under the concentration‐time curve [AUC]) predicted for children with a PBPK model in comparison to the data observed in the first clinical trial with rivaroxaban in children . Another example is the fluoroquinolone antibiotic moxifloxacin the clearance of which was predicted in children by PBPK modeling before the conduction of pediatric trials and compared with individual data observed in 2 pediatric trials .…”
Section: Application Of Pbpk In Pediatric Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows a recent example of PBPK predictions for children that was later confirmed in a clinical trial from a pediatric development program. Figure shows the single‐dose exposure (expressed as area under the concentration‐time curve [AUC]) predicted for children with a PBPK model in comparison to the data observed in the first clinical trial with rivaroxaban in children . Another example is the fluoroquinolone antibiotic moxifloxacin the clearance of which was predicted in children by PBPK modeling before the conduction of pediatric trials and compared with individual data observed in 2 pediatric trials .…”
Section: Application Of Pbpk In Pediatric Researchmentioning
confidence: 99%
“…Figure 3 shows the single-dose exposure (expressed as area under the concentration-time curve [AUC]) predicted for children with a PBPK model 24 in comparison to the data observed in the first clinical trial with rivaroxaban in children. 25 Another example is the fluoroquinolone antibiotic moxifloxacin the clearance of which was predicted in children by PBPK modeling before the conduction of pediatric trials and compared with individual data observed in 2 pediatric trials. [26][27][28] In both case examples, PBPK modeling in children using previous ontogeny information has been proven to be very helpful to guide the development of suitable dosing regimens in pediatric development programs.…”
Section: Established Ontogeny Functionsmentioning
confidence: 99%
“…The PK of a single rivaroxaban dose in children using population PK modeling was assessed in a phase I study. 39,40 In this study, two rivaroxaban dose levels equivalent to adult doses of rivaroxaban 10 and 20 mg, and two different formulations (tablet and oral suspension), were tested in 59 children aged 0.5 to 18 years who had completed treatment for VTE. 39,40 The observed plasma concentration-time profiles in all subjects receiving body-weight-adjusted doses were mostly within the 90% prediction interval, irrespective of dose or formulation.…”
Section: Clinical Pediatric Studiesmentioning
confidence: 99%
“…39,40 In this study, two rivaroxaban dose levels equivalent to adult doses of rivaroxaban 10 and 20 mg, and two different formulations (tablet and oral suspension), were tested in 59 children aged 0.5 to 18 years who had completed treatment for VTE. 39,40 The observed plasma concentration-time profiles in all subjects receiving body-weight-adjusted doses were mostly within the 90% prediction interval, irrespective of dose or formulation. 39 The PD assessment based on PT and aPTT demonstrated that the anticoagulant effect of rivaroxaban was not affected by development hemostasis (►Table 3).…”
Section: Clinical Pediatric Studiesmentioning
confidence: 99%
“…Presently, several direct oral anticoagulants (DOACs) are undergoing evaluation in paediatric development programs [ 68 , 69 , 70 , 71 , 72 , 73 ]. Randomized clinical trials for DOACs in paediatric VTE are ongoing.…”
Section: Treatmentmentioning
confidence: 99%